The Difficult Task of Diagnosing Prostate Cancer Metastases on Dry Bone1. Issue 3 (17th August 2017) - Castoldi, Elisa; Cappella, Annalisa; Gibelli, Daniele; Sforza, Chiarella; Cattaneo, Cristina
Abstract: The interpretation of pathology on skeletal remains is mandatory for implementing the biological profile and for disease recognition. Prostate cancer is one of the most common tumors, with a high preference for the skeleton as a primary site of metastasis. Its diagnosis on bone is however still ambiguous, due to its "osteoblastic" and resorptive manifestation. This study investigates distribution and appearance of prostate cancer metastases on dry bone on six known cases (selected from the Milano Cemetery Skeletal Collection) and one healthy individual. A macroscopic inspection was performed highlighting the abnormalities observed, describing location, shape, dimension, and aspect. A great amount of proliferative and mixed lesions was noticed, but also cases of pure lytic lesions were displayed. The multiple appearances of the manifestations observed display the difficulty in correctly identifying such a pathology, but also the potential and advantages provided by investigating a study sample with known antemortem history.